Antibacterial Activity of Ethyl Acetate and Cream Formulation of Coleus atropurpureus leaves Against Staphylococcus aureus - Tarigan, Indra Lasmana; Muadifah, Afidatul; Susanto, Nindita Clourisa Clourisa Amaris; Huda, Choirul (Brawijaya University, 2021)
Infectious diseases caused by Staphylococcus aureus (Sa) bacteria reaching 70% of cases in Asia and can attack and survive in epithelial cells including endothelial cells. Attempts to overcome the infection caused by Sa by giving antibiotics, which work as antibacterial. Myana (Coleus atropurpureus L. Benth) leaves contain several active compounds that might act as antibacterial agents. This study aimed to analyze the antibacterial activity of Coleus Extract in vitro and to evaluate the formulation of the extract cream against the bacteria causing infection, Sa. Coleus leaves ethyl acetate extract contains alkaloids and tannins, the absorbance of Sa at the 3rd hour was getting smaller, from 0.668 to 0.552, this showed that the longer the incubation time of the extract against bacterial inoculation, the more bacteria died. Our cream formulation with criteria: the pH value, homogeneity, spreadability, adhesion, and protection power. Our cream formulation results were then evaluated based on the standard, with criteria: the pH value, homogeneity, spreadability, adhesion, and protection power. It seems that our cream is per the cream standards. It is semi-solid, brownish-white in color, smells typical of Coleus, and pH 6. Moreover, the cream is homogeneous with 5 cm of spreadability, 7 seconds for adhesion, and colorless. Moreover, we found that Coleus extract cream has better antibacterial activity than positive control with a wound closure time of 7-14 days for extract while more than 14 days for positive control.